Gender Smart Mobility Concepts, Methods, and Practices - Christensen, Hilda Rømer (Transport and Mobility, 2024)
This book presents gender and diversity in smart transport as a cutting-edge issue in urban contexts around the globe. It addresses new challenges and possibilities related to the smart transport sector. It demonstrates how gender and diversity are entangled in concepts and various forms of current smart mobility practices in policy, planning, and innovation. Gender Smart Mobility is presented as a game changer for future transport planning and mobility practices and how smart mobility technologies and practices might be created as a common good for all. The readers are presented with fresh approaches ranging from intersectional and visual analysis of smart mobility, gender scripts and language, to gendered innovation of design and planning. Moreover, the readers will encounter engaging boxed features which present historical, cross-cultural, and methodological examples and pose questions for critical thinking. This book meets a need for a systematic, accessible, and practical introduction and is of interest to city planners, transport providers, and politicians as well as the general public. It will also be a valuable reference for graduate and postgraduate students at technical universities, schools of architecture and planning, and for students and faculties in the social sciences, humanities, and IT and design studies.